Foreign Currency Deposits and International Liquidity Shortages in Pakistan - Mirakhor, Abbas (IMF Working Papers; Working Paper ;, 2004)
This paper studies the implications of foreign currency deposits (FCDs) for international liquidity shortages in Pakistan. The analysis focuses on how the large volume of FCDs and the specific institutional characteristics of those deposits have made the Pakistan economy highly vulnerable to exogenous shocks. The analysis shows that FCDs created another channel for government borrowing, and fiscal sustainability in a "closed" system may be very different from sustainability in a more "open" system. There is a need to think of these issues in terms of total balance sheet vulnerability, and we recommend measures that would make domestic-currency-denominated assets attractive to investors.